UHT processing and aseptic filling of dairy foods - Scott, David L. (Kansas State University, 2008)
The demand for ultra high temperature processed and aseptically packaged dairy foods is growing throughout the U.S. The technology provides value-added food preservation for many foods including flavored milks, puddings, custards, creams, ice-cream mixes, whey-based drinks, sports drinks, and yogurt. Ultra high temperature nonfat milk, milk, light cream, and 18% cream are used throughout the U.S. by the restaurant and food service industries. There are several advantages to aseptic processing and packaging over traditional pasteurization. Advantages include extended shelf life, lower energy costs, and the elimination of required refrigeration during storage and distribution. Challenges are present in all aspects of dairy processing. Major challenges associated with ultra high temperature processing and aseptic packaging of dairy foods include product quality loss, such as age gelation, fat separation, and flavor loss, as well as manufacturing issues such as limited production capacity, potential contamination, slow packaging speeds, and limited shelf life knowledge. This report reviews the history of aseptic processing, principles of ultra high temperature processing, principles of aseptic filling, quality control of UHT dairy foods, and regulations for dairy processors.
Keywords: Aseptic; Ultra high temperature; Dairy; Agriculture, Food Science and Technology (0359)